Uma contribuição ao modelamento analítico em amplificadores Raman - Cani, Shirley Peroni Neves (2007)
The recent advances in high power laser and WDM technologies have contributed to the increasing interest in broadband optical Raman amplifiers. The amplification of signals in such amplifiers occurs due to the stimulated Raman scattering nonlinear effect that occurs along the propagation of pumps and signals in an optical fiber link. The Raman amplifier can be implemented over the entire transmission fiber link, known as distributed Raman amplifier, or over a smaller fiber link in series with the transmission fiber, known as lumped Raman amplifier. One of the challenges in Raman amplifiers is to set the pump power and wavelengths to obtain a desired gain and ripple in a determined signal band. Some methods of optimization have already been proposed, and most of them resort to numerical solutions. This work describes the development of an analytical model of power evolution and signal gain in multi-pumps and multi-signals Raman amplifiers. The analytical model includes in its formulation the Raman interaction among all the frequencies and the polarization effects. Amplified spontaneous emission noise effects and elastic scattering of the light are neglected in the analytical model. The analytical model proposed is validated comparing analytical results with those obtained by numerical solution and experimental data, with a vast combination of input parameters. The comparisons have showed that the analytical model is a reliable and fast tool to design multi-pumps and multi-signal Raman amplifiers.